Effect of aging and Mn substitution on anisotropy of third generation piezoelectrics. (26th October 2018) - Vadapoo, Rajasekarakumar; Ahart, Muhtar; Staruch, Margo; Guerette, Michael; Luo, Jun; Finkel, Peter; Cohen, R. E.
Abstract: We study the aging and Mn doping effect on third generation lead based relaxor single crystals. We measured the polarization (PE) and strain with applied field on two perpendicular orientations of the rhombohedral pseudocubic [001] poled crystal. To understand these effects along the average dipoles/defect dipoles direction, we adopt a simple model with direction cosine and sine of polarization and strain. We found that when the PE measurement is perpendicular to average defect dipoles, a double loop is observed, and when it is parallel an asymmetric response is observed. We propose that the varied response found in PE measurements depend on the relative direction of average dipoles/defect dipoles to the measurement direction.